Succinic acid as a coordination modulator for DMSO-free low-dimensional red-emitting tin perovskites - Akhil Sreevalsan; Woo Hyeon Jeong; Yifan Yu; Cheong Beom Lee; Gunhee Kim; Jongbeom Kim; Hochan Song; Hong In Jeong; Gyeong Eun Seok; Dong-Won Kang; Myoung Hoon Song; Kyeounghak Kim; et al. (Chemical Engineering Journal, 2026)

Probabilistic risk assessment of dietary exposure to acrylamide in Korean adolescents (12–18 years) based on KNHANES 2017–2023 data - Yong-Sik Yoon; Young-Soo Kim; Eun-In Yang; Soon-Il Yun; Sooah Kim (Food Additives & Contaminants: Part A, 2026)

Genome-scale model-guided microbial engineering for valorization of agricultural waste biomass to poly(3-hydroxybutyrate) - Chae-Rim Jeong; Jaeseong Hwang; Young-Kwon Park; Jae Yong Ryu; Yong Hee Han; Ji Young Jeong; In Min Hwang; Ryeongeun Kim; Jung Eun Yang (Bioresource Technology, 2026)

Facile eco-friendly sol-gel synthesis of highly monodispersed Zn@silica nanospheres with dual antibacterial mechanism against multidrug-resistant bacteria - Yesul Jeong; Hyeran Kim; Soon Chang Lee; Ha-Rim An; Jong-Seong Bae; Yunju Choi; Byoungchul Son; Ji-In Park; Da-Hye Kim; Jiwon Seo; Eui-Jeong Han; Ji-Hyun Lee; et al. (Chemical Engineering Journal, 2026)

Baricitinib-loaded separable microneedle array patch (S-MAP) based on hyaluronic acid for alopecia areata therapy - Da In Jeong; Song Yi Lee; Sungyun Kim; Su-Min Jo; HeeSeon Yang; Jieun You; ChaeRim Hwang; Ji Won Huh; Yeoung Eun Choi; Wonjun Jo; In-Jeong Choi; Hae-Jin Hu; et al. (Carbohydrate Polymers, 2025)

Evaluating ripeness in post-harvest stored kiwifruit using VIS-NIR hyperspectral imaging - Jeong-Eun Lee; Min-Jee Kim; Bo-Yeong Lee; Lee Jong Hwan; Ha-Eun Yang; Moon S. Kim; In Geun Hwang; Cheon Soon Jeong; Changyeun Mo (Postharvest Biology and Technology, 2025)

Utilization of coffee waste as a sustainable feedstock for high-yield lactic acid production through microbial fermentation - Seulbi Kim; Jong-Cheol Kim; Yeong Yeol Kim; Jung Eun Yang; Hee Min Lee; In Min Hwang; Hae Woong Park; Ho Myeong Kim (Science of The Total Environment, 2024)

Patterns of δ15N in forest soils and tree foliage and rings between climate zones in relation to atmospheric nitrogen deposition: A review - Woo-Jung Choi; Hyun-Jin Park; Nuri Baek; Hye In Yang; Jin-Hyeob Kwak; Sun-Il Lee; Seo-Woo Park; Eun-Seo Shin; Sang-Sun Lim (Science of The Total Environment, 2023)

Neuregulin-1 suppresses anti-apoptotic effect of Der p 38 on neutrophils by inhibition of cytokine secretion - Yujin Hong; Ji Hyeon Choi; Min Hwa Hong; Geunyeong Kim; Ji-Sook Lee; Ran-Sook Woo; Eun Ju Yang; In Sik Kim (Molecular & Cellular Toxicology, 2023)

Association between SYVN1 and SEL1 genetic polymorphisms and remission in rheumatoid arthritis patients treated with TNF-α inhibitors: a machine learning approach - Woorim Kim; Ha Rim Yeon; Jun Hyeob Kim; Joo Hee Kim; Ji Hyoun Kim; Hyoun-Ah Kim; Ju-Yang Jung; Jinhyun Kim; In Ah Choi; Kyung Eun Lee (Immunologic Research, 2023)

Safety concerns regarding impurities in L-Tryptophan associated with eosinophilia myalgia syndrome - Soo Min Ko; Ji-Eun Park; In Kyung Heo; Yong Uk Shin; Yang Hee Kim; Woo-Chan Son (Food and Chemical Toxicology, 2023)

Phytoplankton succession during a massive coastal diatom bloom at Marian Cove, King George Island, Antarctica - Misa Jeon; José Luis Iriarte; Eun Jin Yang; Sung-Ho Kang; Youngju Lee; Hyoung Min Joo; In-Young Ahn; Jisoo Park; Gi-Sik Min; Sang-Jong Park (Polar Biology, 2021)

First report of tomato mosaic virus infecting chili pepper (Capsicum annuum L.) in Korea - In-Sook Cho; Ju-Yeon Yoon; Eun-Young Yang; Soo-Young Chae; Bong Nam Chung; John Hammond; Hyoun Sub Lim (Journal of Plant Pathology, 2021)

Targeting X chromosome-linked inhibitor of apoptosis protein in mucoepidermoid carcinoma of the head and neck: A novel therapeutic strategy using nitidine chloride - Hye-Jeong Kwon; Kyungsil Yoon; Ji-Youn Jung; Mi Heon Ryu; Sung-Hyun Kim; Eun-Seon Yoo; So-Young Choi; In-Hyoung Yang; Seong Doo Hong; Ji-Ae Shin; Sung-Dae Cho (Journal of Molecular Medicine, 2020)

Coix seed extract attenuates the high-fat induced mouse obesity via PPARγ and C/EBPα a downregulation - Eun-Kyeong Choi; Yu Jeong Cho; Hea Jung Yang; Ki-Suk Kim; In-Seung Lee; Jong-Chan Jang; Kang-Hoon Kim; Ji Hyun Bang; Yumi Kim; Se Hoon Kim; Young-Hwan Cho; Na Young Yoon; et al. (Molecular & Cellular Toxicology, 2015)

Dopamine D4 receptors linked to protein kinase G are required for changes in dopamine release followed by locomotor activity after repeated cocaine administration - Jeong Hwan Oh; Dong Kun Lee; Yoon-Bo Shim; In Soo Ryu; Su Yeon Seo; Jieun Kim; Ju Hwan Yang; Hyun-Wook Cho; Eun Sang Choe (Experimental Brain Research, 2015)

Unveiling abundance and distribution of planktonic B acteria and A rchaea in a polynya in A mundsen S ea, A ntarctica - Jong‐Geol Kim; Soo‐Je Park; Zhe‐Xue Quan; Man‐Young Jung; In‐Tae Cha; So‐Jeong Kim; Kyoung‐Ho Kim; Eun‐Jin Yang; Young‐Nam Kim; Sang‐Hoon Lee; Sung‐Keun Rhee (Environmental Microbiology, 2014)
Summary Polynyas, areas of open water surrounded by sea ice, are sites of intense primary production and ecological hotspots in the A ntarctic O cean. This study determined the spatial variation in communities of prokaryotes in a polynya in the A mundsen S ea using 454 pyrosequencing technology, and the results were compared with biotic and abiotic environmental factors. The bacterial abundance was correlated with that of phytoplankton, P haeocystis spp. and diatoms. A cluster analysis indicated that the bacterial communities in the surface waters of the polynya were distinct from those under the sea ice. Overall, two bacterial clades, P olaribacter (20–64%) and uncultivated O ceanospirillaceae (7–34%), dominated the surface water in the polynya while the P elagibacter clade was abundant at all depths (7–42%). The archaeal communities were not as diverse as the bacterial communities in the polynya, and marine group I was dominant (> 80%). Canonical correspondence analysis indicated that the oceanographic properties facilitated the development of distinct prokaryotic assemblages in the polynya. This analysis of the diversity and composition of the psychrophilic prokaryotes associated with high phytoplankton production provides new insights into the roles of prokaryotes in biogeochemical cycles in high‐latitude polynyas.

Enhanced regeneration of rabbit mandibular defects through a combined treatment of electrical stimulation and rhBMP-2 application - Junghoon Kim; Hoon Joo Yang; Tae Hyung Cho; Sung Eun Lee; Yong Doo Park; Hyun Man Kim; In Sook Kim; Young-kwon Seo; Soon Jung Hwang; Sung June Kim (Medical & Biological Engineering & Computing, 2013)

Treadmill exercise represses neuronal cell death and inflammation during Aβ-induced ER stress by regulating unfolded protein response in aged presenilin 2 mutant mice - Eun-Bum Kang; In-Su Kwon; Jung-Hoon Koo; Eung-Joon Kim; Chul-Hyun Kim; Jin Lee; Choon-Ho Yang; Young-Il Lee; In-Ho Cho; Joon-Yong Cho (Apoptosis, 2013)

Physicochemical properties and antioxidant activity of Korean cactus (Opuntia humifusa) cladodes - Hyun-Il Jun; Mi-Na Cha; Eun-In Yang; Dong Geun Choi; Young-Soo Kim (Horticulture, Environment, and Biotechnology, 2013)

p53 acetylation enhances Taxol-induced apoptosis in human cancer cells - Jae Hyeong Kim; Eun-Kyung Yoon; Hye-Jin Chung; Seong-Yeol Park; Kyeong-Man Hong; Chang-Hun Lee; Yeon-Su Lee; Kyungho Choi; Young Yang; Kyungtae Kim; In-Hoo Kim (Apoptosis, 2013)

Hydroquinone-induced apoptosis of human lymphocytes through caspase 9/3 pathway - Ji-Sook Lee; Eun Ju Yang; In Sik Kim (Molecular Biology Reports, 2012)

Hepatoprotection of different water extracts from Acer tegmentosum M. on CCl4-induced acute hepatotoxicity in mice: comparative efficacies between the extracts of boughs, twigs, and leaves - Kwang-Yong Shim; Dong-Heui Kim; Soon-Bong Song; Xu-Feng Qi; Yang-Suk Yoon; Hyun-Soo Kim; Jong-In Lee; Hwa-Eun Oh; Soo-Ki Kim; Kyu-Jae Lee (Molecular & Cellular Toxicology, 2011)

The effects of benzene and toluene on leukotactin-1-induced migration of EoL-1 cells - Bo Bae Song; Eun Ju Yang; Bo-Mi Kim; Ji-Sook Lee; Chi-Young Yun; Yang-Bin Im; In Sik Kim (Molecular & Cellular Toxicology, 2011)

Comparative study of the chemical composition and antioxidant activity of six essential oils and their components - Seun-Ah Yang; Sang-Kyung Jeon; Eun-Jung Lee; Chang-Hyun Shim; In-Seon Lee (Natural Product Research, 2010)